2017
DOI: 10.1055/s-0037-1607436
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non–Vitamin K Antagonist Oral Anticoagulants in Atrial Fibrillation Patients with Malignancy: Clinical Practice Experience in a Single Institution and Literature Review

Abstract: This observational study aimed to investigate the efficacy and safety of non-vitamin K antagonist oral anticoagulants (NOACs) in atrial fibrillation (AF) patients with malignancy. A total of 76 patients (mean age: 73.2 ± 8.9; 28 females) with AF and malignancy treated with NOAC were included in the analysis. The mean CHADS-VASc and HAS-BLED scores were 3.2 ± 1.2 and 2.2 ± 0.9, respectively. The study population was taking dabigatran 150 mg (25%) twice daily (BID), apixaban 5 mg BID (25%), dabigatran 110 mg BID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…NOACs are safe and effective alternatives to VKA therapy [46,47,48,49], and are currently considered as first-line therapy for long-term stroke prevention in patients with nonvalvular AF [6]. The overall safety and efficacy profile of NOACs have been confirmed in different clinical scenarios [50,51,52,53,54,55,56,57,58]. The clinical performance of NOACs in the setting of acute and elective CV has been addressed by three prospective randomized trials.…”
Section: Prevention and Treatment Of Left Atrial Appendage Thrombosismentioning
confidence: 99%
“…NOACs are safe and effective alternatives to VKA therapy [46,47,48,49], and are currently considered as first-line therapy for long-term stroke prevention in patients with nonvalvular AF [6]. The overall safety and efficacy profile of NOACs have been confirmed in different clinical scenarios [50,51,52,53,54,55,56,57,58]. The clinical performance of NOACs in the setting of acute and elective CV has been addressed by three prospective randomized trials.…”
Section: Prevention and Treatment Of Left Atrial Appendage Thrombosismentioning
confidence: 99%
“…The evaluation of apixaban serum level at peak and trough time demonstrated the therapeutic drug levels in our morbid obese patient and the stability of apixaban plasma levels even when the patient has lost weight. The use of plasma level monitoring for NOAC doseadjustment is discouraged for the vast majority of patients due to the lack of outcome data to support such an approach; however, in rare cases of potentially substantial drug-drug interactions; 23,24 in special population in which the use of NOACs is still debated, 25,26 or in case of not deferrable cardiac or non-cardiac interventional or surgical procedures, 27 a "patient-centered approach", including the plasmatic drug evaluation, might be considered for choosing the more appropriate anticoagulant molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the induction of the anticoagulant effect is eased without having to resort to the administration of heparin [28,29]. Moreover, both the safety and efficacy of NOACs have been positively tested in a randomized clinical trial [30] and confirmed by several clinical real-world casuistries [1,31,32,33,34,35].…”
Section: Novel Oral Anticoagulants (Noacs): a Future Already Presentmentioning
confidence: 99%
“…However, this class of drugs is burdened by the need to maintain the INR at target. In the last few years, with the advent of NOACs, several studies have assessed the safety and efficacy in this specific population [32,55,56,57,58]. Nevertheless, the limited sample size and the wide spectrum of malignancies render it necessary to conduct further in-depth studies.…”
Section: Anticoagulant Therapy: An Upcoming Challengementioning
confidence: 99%